Understanding global terror - Ankersen, Christopher; O'Leary, Michael (Cambridge ; Malden, MA : Polity, 2007)
This book explores global terror from a range of perspectives - from the impact of terrorism on the international system to the American 'War on Terror' and the individual motivations of the suicide bomber. Core themes such as the funding of terrorist groups and the roles of intelligence-gathering and international law in combating terrorism are fully explored. The volume also offers in-depth analyses of the relationship between globalization and terrorism as well as regional and country-based responses to the rise of terrorist networks in Europe, Russia, Southeast Asia and Africa.
Introduction / Christopher Ankersen -- Global terror and the international community / Chris Brown -- Explaining suicide terrorism / Ami Pedahzur, Arie Perliger, and Alexander Bialsky -- The imperial republic in an age of war : the United States from September 11 to Iraq / Michael Cox -- Europe and the war on terror / William Wallace -- Russia and the war on terrorism / Margot Light -- Southeast Asia and global terror / Kerry Lynn Nankivell and James Boutilier -- From terrorism to human security in Africa / Timothy M. Shaw -- Terrorism and international law / Dinah PoKempner -- Global terror and international finance in the immediate aftermath of 9/11 / Martin S. Navias -- Intelligence and international security after 9/11 / Christopher Mackmurdo -- Globalization and the war against terrorism / Lawrence Freedman.
Includes bibliographical references and index.
Keywords: 2001-2009; Terrorism; Terrorists; War on Terrorism, 2001-2009.; Terrorism and globalization; Terrorism and globalization